Electrochemical hydrogen and electricity production by using anodes made of commercial aluminum. (15th January 2019) - Raptis, Dimitrios; Seferlis, Andreas K.; Mylona, Vasiliki; Politis, Constantin; Lianos, Panagiotis
Abstract: Two commercial aluminum alloys have been studied as anodes for simultaneous electrochemical hydrogen and electricity production, as compared with pure aluminum. Both are very active in corrosive hydrogen production and functional as anodes in aluminum-air batteries. Both produced approximately 3 times more hydrogen than pure aluminum while their electrochemical characteristics were substantially preserved with only small modifications with respect to pure aluminum. Devices employing commercial aluminum anodes can be constructed and may be used for producing both hydrogen and electricity at the expense of aluminum. Graphical abstract: "Electrochemical hydrogen and electricity production by using anodes made of commercial aluminum" by Raptis et al. Highlights: Study of two commercial Al alloys by comparison to pure aluminum. Hydrogen production by aluminum corrosion. Electricity production in an Al-air battery configuration. Construction of a preliminary device simultaneously producing electricity and hydrogen.